Dissecting halo components in IFU data - Merrifield, Michael; Johnston, Evelyn; Aragón-Salamanca, Alfonso (MDPI, 2017)
While most astronomers are now familiar with tools to decompose images into multiple components such as disks, bulges, and halos, the equivalent techniques for spectral data cubes are still in their infancy. This is unfortunate, as integral field unit (IFU) spectral surveys are now producing a mass of data in this format, which we are ill-prepared to analyze effectively. We have therefore been developing new tools to separate out components using this full spectral data. The results of such analyses will prove invaluable in determining not only whether such decompositions have an astrophysical significance, but, where they do, also in determining the relationship between the various elements of a galaxy. Application to a pilot study of IFU data from the cD galaxy NGC 3311 confirms that the technique can separate the stellar halo from the underlying galaxy in such systems, and indicates that, in this case, the halo is older and more metal poor than the galaxy, consistent with it forming from the cannibalism of smaller satellite galaxies. The success of the method bodes well for its application to studying the larger samples of cD galaxies that IFU surveys are currently producing.